Adipose-Derived Stem Cell Sheets Improve Early Biomechanical Graft Strength in Rabbits After Anterior Cruciate Ligament Reconstruction. Issue 13 (November 2021) - Matsumoto, Tatsuaki; Sato, Yuiko; Kobayashi, Tami; Suzuki, Kunika; Kimura, Atsushi; Soma, Tomoya; Ito, Eri; Kikuchi, Toshiyuki; Kobayashi, Shu; Harato, Kengo; Niki, Yasuo; Matsumoto, Morio; et al.
Background: Although various reconstruction techniques are available for anterior cruciate ligament (ACL) injuries, a long recovery time is required before patients return to sports activities, as the reconstructed ACL requires time to regain strength. To date, several studies have reported use of mesenchymal stem cells in orthopaedic surgery; however, no studies have used adipose-derived stem cell (ADSC) sheets in ACL reconstruction (ACLR). Hypothesis: ADSC sheet transplantation can improve biomechanical strength of the autograft used in ACLR. Study Design: Controlled laboratory study. Methods: A total of 68 healthy Japanese white rabbits underwent unilateral ACLR with a semitendinosus tendon autograft after random enrollment into a control group (no sheet; n = 34) and a sheet group (ADSC sheet; n = 34). At 2, 4, 8, 16, and 24 weeks after surgery, rabbits in each group were sacrificed to evaluate tendon-bone healing using histological staining, micro–computed tomography, and biomechanical testing. At 24 weeks, scanning transmission electron microscopy of the graft midsubstance was performed. Results: The ultimate failure load for the control and sheet groups, respectively, was as follows: 17.2 ± 5.5 versus 37.3 ± 10.3 ( P = .01) at 2 weeks, 28.6 ± 1.9 versus 47.4 ± 10.4 ( P = .003) at 4 weeks, 53.0 ± 14.3 versus 48.1 ± 9.3 ( P = .59) at 8 weeks, 66.2 ± 9.3 versus 95.2 ± 43.1 ( P = .24) at 16 weeks, and 66.7 ± 27.3 versus 85.3 ± 29.5 ( P = .39) at 24 weeks. The histological score was also significantly higher in the sheet group compared with the control group at early stages up to 8 weeks. On micro–computed tomography, relative to the control group, the bone tunnel area was significantly narrower in the sheet group at 4 weeks, and the bone volume/tissue volume of the tendon-bone interface was significantly greater at 24 weeks. Scanning transmission electron microscopy at 24 weeks indicated that the mean collagen fiber diameter in the midsubstance was significantly greater, as was the occupation ratio of collagen fibers per field of view, in the sheet group. Conclusion: ADSC sheets improved biomechanical strength, prevented bone tunnel enlargement, and promoted tendon-bone interface healing and graft midsubstance healing in an in vivo rabbit model. Clinical Relevance: ADSC sheets may be useful for early tendon-bone healing and graft maturation in ACLR.